Growth Dynamics of Young Avocado (Persea americana Mill) Plants under Drought Stress in Potted Condition - Rumaisha, Azizah; Susanto, Slamet; Tirtawinata, Mohamad Reza (Department of Agronomy and Horticulture, IPB University, 2025)
Drought stress significantly influences plant metabolic processes, including overall vegetative growth and the transition from the vegetative to the generative phase. Under changing environmental conditions, plants adapt through specific mechanisms to survive unfavorable circumstances, including a reduction in the juvenile phase. This study aimed to examine the effects of drought stress on the growth dynamics of young avocado plants. The experiment consisted of three treatment levels: routine watering as the control (P1), drought stress for 8 weeks (P2), and drought stress for 16 weeks (P3). The 8 week drought stress did not significantly reduce the number of leaves or increase the number of vegetative buds; however, one plant produced flowers at week 33. The drought stress for 16 weeks (P3) significantly reduced the number of leaves but did not affect branch length. Instead, it increased the number of vegetative buds per branch at 16 and 24 weeks after treatment (WAT). Drought stressed plants exhibited a compensatory growth mechanism following rewatering, as demonstrated by an increase in the number of leaves and vegetative buds at 24 WAT.